The SH2/SH3 domain-containing protein GRB2 interacts with tyrosine-phosphorylated IRS1 and Shc: implications for insulin control of ras signalling. - Skolnik, E Y (1993)
GRB2, a small protein comprising one SH2 domain and two SH3 domains, represents the human homologue of the Caenorhabditis elegans protein, sem-5. Both GRB2 and sem-5 have been implicated in a highly conserved mechanism that regulates p21ras signalling by receptor tyrosine kinases. In this report we show that in response to insulin, GRB2 forms a stable complex with two tyrosine-phosphorylated proteins. One protein is the major insulin receptor substrate IRS-1 and the second is the SH2 domain-containing oncogenic protein, Shc. The interactions between GRB2 and these two proteins require ligand activation of the insulin receptor and are mediated by the binding of the SH2 domain of GRB2 to phosphotyrosines on both IRS-1 and Shc. Although GRB2 associates with IRS-1 and Shc, it is not tyrosine-phosphorylated after insulin stimulation, implying that GRB2 is not a substrate for the insulin receptor. Furthermore, we have identified a short sequence motif (YV/IN) present in IRS-1, EGFR and Shc, which specifically binds the SH2 domain of GRB2 with high affinity. Interestingly, both GRB2 and phosphatidylinositol-3 (PI-3) kinase can simultaneously bind distinct tyrosine phosphorylated regions on the same IRS-1 molecule, suggesting a mechanism whereby IRS-1 could provide the core for a large signalling complex. We propose a model whereby insulin stimulation leads to formation of multiple protein--protein interactions between GRB2 and the two targets IRS-1 and Shc. These interactions may play a crucial role in activation of p21ras and the control of downstream effector molecules.